2016
DOI: 10.1016/j.molcata.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Nitrobenzene-assisted reduction of phenylacetylene with hydrazine over nitrogen-doped metal-free activated carbon catalyst: Significance of interactions among substrates and catalyst

Abstract: A nitrogen-doped activated carbon (AC) can catalyze the reduction of nitrobenzene with hydrazine but not phenylacetylene. When nitrobenzene coexists in the reaction mixture, however, phenylacetylene can also be reduced. Nitrobenzene is likely to assist the adsorption of phenylacetylene on the surface of AC catalyst through molecular interactions between the two substrates, allowing their simultaneous reduction to aniline and styrene. For these interactions to occur, nitrogen and/or oxygen species doped on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The enhancement in the selectivity is explained by interactions between the modifiers and the substrates on the surface of supported Pt particles, similar to our case in which interactions between CAL and a product of HCAL on the surface of PdZn catalyst are responsible for the increase in the COL selectivity during the reaction. Recently, the present authors reported a similar phenomenon for the reduction of nitrobenzene and phenylacetylene with hydrazine over a nitrogen-and oxygen-doped metal-free activated carbon (AC) catalyst [39].…”
Section: Surface Properties Of Pdzn and Pd Catalystssupporting
confidence: 56%
“…The enhancement in the selectivity is explained by interactions between the modifiers and the substrates on the surface of supported Pt particles, similar to our case in which interactions between CAL and a product of HCAL on the surface of PdZn catalyst are responsible for the increase in the COL selectivity during the reaction. Recently, the present authors reported a similar phenomenon for the reduction of nitrobenzene and phenylacetylene with hydrazine over a nitrogen-and oxygen-doped metal-free activated carbon (AC) catalyst [39].…”
Section: Surface Properties Of Pdzn and Pd Catalystssupporting
confidence: 56%
“…The promotional effect of the nitro group was further investigated for the hydrogenation of the ethynyl group of phenylacetylene (PA) (Scheme 7d) by using one selected N-OAC [15]. In the absence of catalyst, the hydrogenation of PA alone occurred at a small extent (4%).…”
Section: Use Of Nitrogen-doped Activated Carbon For Transfer Hydrogenmentioning
confidence: 99%
“…It is highly probable that interactions between PA and NB occur, allowing PA to be adsorbed and reduced on the surface of N-OAC. Possible interactions were proposed to occur between C≡C bond and O-N bonds (Scheme 9) [15], in which O and N could originate from both NB and the surface species on N-OAC. Interactions between PA and adsorbed hydrazine might also contribute to the PA hydrogenation assisted by NB.…”
Section: Use Of Nitrogen-doped Activated Carbon For Transfer Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…As catalyst supports, NCMs can improve the sur-face charge density of metal particles, such as: Co [6] and Ru [7], which facilitates the catalytic activity. Recent studies indicate that NCMs can be directly used as catalysts for some heterogeneous catalytic reactions, such as: dehydrogenation of ethylbenzene [8], the catalytic reductions of nitrobenzene [9] or phenylacetylene [10], catalytic oxidation of ethylbenzene to acetophenone [11], and catalytic hydrogen chlorination of acetylene [12]. Compared with metal-loaded NCMs, metal-free NCMs would not suffer from the aggregation and loss of metal particles, which are certain disadvantages for metallic catalysts [13].…”
Section: Introductionmentioning
confidence: 99%